Organic photovoltaic devices incorporating nanostructures in the photoactive layer: Towards clean solar energy generation - Sulaiman, K.; Fakir, M.S.; Yusli, M.N.; Abd. Wahab, F. (2011)

(untitled)
In this article we report the nanostructures formation in the thin films of several organic semiconductors. The thin films have been deposited onto glass substrates by a solution processable of spin-coating technique. The nanostructures are obtained by applying a simple surface solvent treatment process either by soaking or solvent vapor treatment. The influence of solvent treatment on the surface morphological properties has been investigated via a surface profilometer, absorption spectroscopy, Xray Diffraction Spectroscopy and Atomic Force Microscopy (AFM). It reveals that the spin-coated TsCuPc thin films have nanostructures as evident from the surface profile image, which then confirmed by AFM image. Besides, the polymer chains have been re-organized after solvent treatment and the crystallinity is increased. Such crystalline increment provides a better pathway for charge carrier transport. The photovoltaic performance has improved to some extent for the device containing nano-structured film. We infer this enhancement is due to a larger interface area for exciton dissociation to generate free charge carriers of electrons and holes within the nanostructured film.